Predicting the present and future of aquaponics - Dos Santos, Maria José Palma Lampreia (2017)
Nowadays the increasing volumes of ‘big data’ reflecting various aspects of our present activities and represent a crucial new opportunity for scientists and experts to study the fundamental questions about the complex world we inhabit (Preis et al., 2013; Axtell, R. L. Zipf, 2001; King 2011; Vespignani, 2009; Perc, 2012; Petersen et al., 2012; Christakis et al., 2009). On the other hand, research on innovative topics, whose technology is still in constant progress, development and improvement of efficiency on the use of inputs and the production of outputs like is the case of aquaponics in Europe, sometimes results in difficulties in obtaining data. These difficulties arise, or because there is no data available from private companies, or because either there are data from other continents, or countries whose production systems do not allow comparability, or because the soil-climatic conditions, or technical-institutional-economic conditions (Goddek, et al. (2015; Dos Santos. 2016). Because they use different production techniques due to the difference in quality and quantity of inputs available in loco.